Laminated ceramic capacitor and method of manufacturing laminated ceramic capacitor

The multilayer ceramic capacitor design addresses capacitance loss and densification issues by optimizing sintering aid distribution, maintaining capacitance and densifying the ceramic layer at low temperatures.

JP2025006578APending Publication Date: 2025-01-17TAIYO YUDEN KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023107462
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The use of sintering aids in multilayer ceramic capacitors leads to a decrease in capacitance due to their lower dielectric constant, while insufficient sintering at low temperatures results in inadequate densification of ceramic layers.

Method used

A multilayer ceramic capacitor design with a ceramic layer containing a sintering aid element, where the concentration of the sintering aid is higher in non-electrode portions and intermediate layers, promoting effective discharge of the sintering aid to maintain capacitance and densify the ceramic layer at low temperatures.

Benefits of technology

The design effectively suppresses capacitance loss and ensures densification of the ceramic layer, enhancing the performance of the multilayer ceramic capacitor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025006578000001_ABST
    Figure 2025006578000001_ABST
Patent Text Reader

Abstract

To provide a laminated ceramic capacitor having a capacitance less reduced by a sintering aid.SOLUTION: A laminated ceramic capacitor according to one aspect of the present invention includes a body having a first internal electrode layer, a second internal electrode layer, and a ceramic layer disposed between the first internal electrode layer and the second internal electrode layer. The ceramic layer is formed from a ceramic material with an added sintering aid that contains a sintering aid element as main components. The body is provided with a first external electrode so as to be electrically connected to the first internal electrode layer. In addition, the body is provided with a second external electrode so as to be electrically connected to the second internal electrode layer. The first internal electrode layer includes an electrode part that is a sintered compact of main component metal elements, and a non-electrode part that is surrounded by the electrode part. The non-electrode part contains the sintering agent element. A first concentration indicating a concentration of the sintering aid element in the non-electrode part is higher than a second concentration indicating a concentration of the sintering aid element in an interface between the first internal electrode layer and the ceramic layer.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The disclosure of the present specification mainly relates to a multilayer ceramic capacitor and a method for manufacturing the multilayer ceramic capacitor. The disclosure of the present specification also relates to a circuit module including the multilayer ceramic capacitor and an electronic device including the circuit module. [Background technology]

[0002] Multilayer ceramic capacitors are used in various electronic devices. Multilayer ceramic capacitors are produced by stacking laminate units, each having an internal electrode pattern formed on the surface of a ceramic green sheet containing ceramic powder, to form a green laminate, and then firing the green laminate. It is known that adding a sintering aid to the ceramic green sheet can promote sintering of the ceramic powder by firing at a low temperature. Known examples of sintering aids include Si (silicon), which becomes liquid during firing. A conventional multilayer ceramic capacitor produced using ceramic green sheets to which a sintering aid has been added is described in JP 2009-084111 A. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2009-084111 A Summary of the Invention [Problem to be solved by the invention]

[0004] Since the sintering aid has a lower dielectric constant than the main phase oxide (e.g., barium titanate) of the ceramic green sheet, the capacitance of the multilayer ceramic capacitor decreases when the amount of the sintering aid is increased. On the other hand, when the amount of the sintering aid is small, the ceramic layer does not become sufficiently dense when the green laminate is sintered at a low temperature.

[0005] It is an object of the invention disclosed in this specification to solve or alleviate at least some of the above-mentioned problems. A more specific object of the invention disclosed in this specification is to provide a multilayer ceramic capacitor in which a decrease in capacitance due to a sintering aid is suppressed.

[0006] Objects of the present invention other than those mentioned above will become clear throughout the entire description of the specification. The invention disclosed in this specification may solve problems that are understood from other than the description in the "Problems to be Solved by the Invention" column. When the effects of an embodiment are described in this specification, the problems of the invention corresponding to the embodiment can be understood from the effects. [Means for solving the problem]

[0007] Various inventions disclosed in this specification may be simply referred to as "the present invention". A multilayer ceramic capacitor in one aspect of the present invention includes a body having a first internal electrode layer, a second internal electrode layer, and a ceramic layer disposed between the first internal electrode layer and the second internal electrode layer. The ceramic layer is formed of a ceramic material to which a sintering aid containing a sintering aid element as a main component is added. A first external electrode is provided on the body so as to be electrically connected to the first internal electrode layer. Also, a second external electrode is provided on the body so as to be electrically connected to the second internal electrode layer. The first internal electrode layer has an electrode portion which is a sintered body of a main component metal element, and a non-electrode portion surrounded by the electrode portion. The non-electrode portion contains a sintering aid element. A first concentration indicating the concentration of the sintering aid element in the non-electrode portion is higher than a second concentration indicating the concentration of the sintering aid element at the interface between the first internal electrode layer and the ceramic layer. Effect of the Invention

[0008] According to one embodiment of the invention disclosed in this specification, it is possible to provide a multilayer ceramic capacitor in which a decrease in capacitance caused by a sintering additive is suppressed. [Brief description of the drawings]

[0009] [Figure 1] 1 is a perspective view showing a schematic diagram of a multilayer ceramic capacitor according to an embodiment of the present invention; [Diagram 2] 2 is a cross-sectional view that illustrates a schematic cross section of the capacitor of FIG. 1 taken along line II. [Diagram 3] 3 is an enlarged cross-sectional view showing a part (area A) of the cross section of FIG. 2 in an enlarged manner. [Figure 4] 3 is an enlarged cross-sectional view showing a part (region B) of the cross section of FIG. 2 in an enlarged manner. [Diagram 5] FIG. 2 is a flow chart showing the flow of a method for manufacturing a multilayer ceramic capacitor according to an embodiment of the present invention. [Figure 6a] 1A to 1C are schematic diagrams illustrating a process for producing a composite ceramic capacitor. [Figure 6b] 1A to 1C are schematic diagrams illustrating a process for producing a composite ceramic capacitor. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Various embodiments of the present invention will be described below with reference to the drawings as appropriate. Components common to multiple drawings are given the same or similar reference symbols throughout the multiple drawings. Please note that the drawings are not necessarily drawn to scale for the sake of convenience. The embodiments described below do not necessarily limit the invention according to the claims. Elements described in the following embodiments are not necessarily essential to the solution of the invention.

[0011] For ease of explanation, each drawing may include an L axis, a W axis, and a T axis that are perpendicular to each other. In this specification, the dimensions, arrangement, shape, and other features of each component of the multilayer ceramic capacitor 1 may be explained based on the L axis, the W axis, and the T axis.

[0012] 1 Multilayer ceramic capacitor 1 1-1 Basic structure of multilayer ceramic capacitor 1 The basic structure of the multilayer ceramic capacitor 1 in accordance with the first embodiment will be described with reference to Fig. 1 and Fig. 2. Fig. 1 is a perspective view of the multilayer ceramic capacitor 1 in accordance with the first embodiment. Fig. 2 is a cross-sectional view that typically shows a cross section of the multilayer ceramic capacitor 1 taken along line II.

[0013] The multilayer ceramic capacitor 1 includes a main body 10, and a first external electrode 31 and a second external electrode 32 provided on the main body 10. The first external electrode 31 is disposed spaced apart from the second external electrode 32. In the example shown in Fig. 2, the first external electrode 31 is disposed spaced apart from the second external electrode 32 in the L-axis direction.

[0014] The main body 10 includes a plurality of ceramic layers 11, a plurality of first internal electrode layers 21, and a plurality of second internal electrode layers 22. The ceramic layer 11 is disposed between the first internal electrode layer 21 and the second internal electrode layer 22 adjacent to the first internal electrode layer 21. In this specification, when it is not necessary to distinguish the first internal electrode layer 21 and the second internal electrode layer 22 from each other, the first internal electrode layer 21 and the second internal electrode layer 22 may be collectively referred to as "internal electrode layers".

[0015] The main body 10 has an upper surface 10a, a lower surface 10b, a first end surface 10c, a second end surface 10d, a first side surface 10e, and a second side surface 10f. The outer surface of the main body 10 is defined by the upper surface 10a, the lower surface 10b, the first end surface 10c, the second end surface 10d, the first side surface 10e, and the second side surface 10f.

[0016] The upper surface 10a and the lower surface 10b form the surfaces at both ends of the main body 10 in the height direction (T-axis direction). In other words, the upper surface 10a and the lower surface 10b face each other in the T-axis direction. The first end surface 10c and the second end surface 10d form the surfaces at both ends of the main body 10 in the length direction (L-axis direction). In other words, the first end surface 10c and the second end surface 10d face each other in the L-axis direction. The first side surface 10e and the second side surface 10f form the surfaces at both ends of the main body 10 in the width direction (W-axis direction). In other words, the first side surface 10e and the second side surface 10f face each other in the W-axis direction. The upper surface 10a and the lower surface 10b are spaced apart by the height dimension of the main body 10, the first end surface 10c and the second end surface 10d are spaced apart by the length dimension of the main body 10, and the first side surface 10e and the second side surface 10f are spaced apart by the width dimension of the main body 10.

[0017] The main body 10 is constructed by stacking the ceramic layers 11, the first internal electrode layers 21, and the second internal electrode layers 22 along a stacking direction. In the illustrated embodiment, the ceramic layers 11, the first internal electrode layers 21, and the second internal electrode layers 22 are stacked along the T-axis direction. The stacking direction may be along the T-axis as illustrated, or along the L-axis or W-axis. The ceramic layers 11 arranged at both ends in the stacking direction may be called cover layers.

[0018] In the illustrated embodiment, the main body 10 is constructed by stacking the ceramic layers 11, the first internal electrode layers 21, and the second internal electrode layers 22 along the T-axis direction. For this reason, the T-axis direction may be referred to as the stacking direction. An upper cover layer may be provided on the upper surface of this stack. A lower cover layer may be provided on the lower surface of this stack. The upper cover layer and the lower cover layer may be made of the same material as the ceramic layers 11. The upper cover layer and the lower cover layer may be part of the main body 10.

[0019] One end of the first internal electrode layer 21 is drawn toward the outside of the main body 10. The first internal electrode layer 21 is connected to a first external electrode 31 provided on the surface of the main body 10. One end of the second internal electrode layer 22 is drawn toward the outside of the main body 10. The second internal electrode layer 22 is connected to a second external electrode 32 provided on the surface of the main body 10. In the illustrated embodiment, the first internal electrode layer 21 is drawn toward the outside of the main body 10 from one end in the L-axis direction. The first internal electrode layer 21 is connected to the first external electrode 31 at one end in the L-axis direction of the main body 10. The second internal electrode layer 22 is drawn toward the outside of the main body 10 from the other end in the L-axis direction. The second internal electrode layer 22 is connected to the second external electrode 32 at the other end in the L-axis direction of the main body 10. 2, the first internal electrode layer 21 and the second internal electrode layer 22 are respectively drawn out to the opposing first end surface 10c and second end surface 10d, but the first internal electrode layer 21 and the second internal electrode layer 22 may be drawn out from various surfaces of the main body 10 depending on the arrangement and shape of the first external electrode 31 and the second external electrode 32. For example, when the first external electrode 31 and the second external electrode 32 are both arranged on the lower surface 10b, the first external electrode 31 and the second external electrode 32 are both drawn out from the lower surface. The first external electrode 31 and the second external electrode 32 may be provided on any surface of the main body 10 as long as they are spaced apart from each other.

[0020] When a voltage is applied between the first external electrode 31 and the second external electrode 32 , a capacitance is generated between the first internal electrode layer 21 and the second internal electrode layer 22 .

[0021] As described later, a first intermediate layer 51 may be disposed between the ceramic layer 11 and the first internal electrode layer 21, and a second intermediate layer 52 may be disposed between the ceramic layer 11 and the second internal electrode layer 22. In Fig. 1 and Fig. 2, the first intermediate layer 51 and the second intermediate layer 52 are omitted from illustration. In this specification, when there is no need to distinguish the first intermediate layer 51 and the second intermediate layer 52 from each other, the first intermediate layer 51 and the second intermediate layer 52 may be collectively referred to as "intermediate layer".

[0022] 2, for the sake of simplicity, five layers each of the first internal electrode layers 21 and the second internal electrode layers 22 are shown, but the multilayer ceramic capacitor 1 can have any number of laminations. For example, the multilayer ceramic capacitor 1 can have 300 to 1000 layers of the first internal electrode layers 21 and the second internal electrode layers 22. In other words, the number of laminations in the multilayer ceramic capacitor 1 can be 300 to 1000 layers.

[0023] The multilayer ceramic capacitor 1 can be mounted on an electronic circuit board (not shown). The electronic circuit board on which the multilayer ceramic capacitor 1 is mounted is sometimes called a circuit module. Various electronic components other than the multilayer ceramic capacitor 1 can also be mounted on the circuit module. This circuit module can be mounted in various electronic devices. Electronic devices in which the circuit module can be mounted include smartphones, tablets, game consoles, automotive electrical equipment, servers, and various other electronic devices.

[0024] In one embodiment, the main body 10 may be configured to have a rectangular parallelepiped shape. In this specification, the term "rectangular parallelepiped" or "rectangular parallelepiped shape" does not mean only a "rectangular parallelepiped" in the strict mathematical sense. As described below, the corners and / or sides of the main body 10 may be curved. The dimensions and shapes of the main body 10 are not limited to those explicitly described in this specification.

[0025] In one embodiment, the dimension (length dimension) of the multilayer ceramic capacitor 1 in the L-axis direction is in the range of 0.2 mm to 2.5 mm, the dimension (width dimension) in the W-axis direction is in the range of 0.1 mm to 3.5 mm, and the dimension (height dimension) in the T-axis direction is in the range of 0.1 mm to 3.0 mm. In one embodiment, the length dimension of the multilayer ceramic capacitor 1 may be greater than the width dimension. In one embodiment, the height dimension of the multilayer ceramic capacitor 1 may be greater than the width dimension. In one embodiment, the width dimension of the multilayer ceramic capacitor 1 may be greater than the length dimension.

[0026] 1-2 First internal electrode layer 21 and second internal electrode layer 22 1-2-1 Composition of the first internal electrode layer 21 and the second internal electrode layer 22 In one embodiment, the first internal electrode layer 21 contains a base metal such as Ni (nickel), Cu (copper), or Sn (tin) as a main component. Based on the total mass of the first internal electrode layer 21, a component contained in the first internal electrode layer 21 at 50 wt% or more can be the main component of the first internal electrode layer 21. The first internal electrode layer 21 desirably contains 60 wt% or more, 70 wt% or more, 80 wt% or more, or 90 wt% or more of the base metal as the main component.

[0027] The first internal electrode layer 21 may contain a sub-element in addition to the main component metal element. The sub-element that may be contained in the first internal electrode layer 21 is, for example, one element or two or more elements selected from the group consisting of As (arsenic), Au (gold), Co (cobalt), Cr (chromium), Cu, Fe (iron), In (indium), Ir (iridium), Mg (magnesium), Os (osmium), Pd (palladium), Pt (platinum), Re (rhenium), Rh (rhodium), Ru (ruthenium), Se (selenium), Sn, Ge (germanium), Te (tellurium), W (tungsten), Y (yttrium), Ag (silver), and Mo (molybdenum). However, the main component metal element and the sub-element are different elements. For example, when the main component metal element is Ni, Sn can be used as the sub-element, but when the main component metal element is Sn, Sn cannot be selected as the sub-element.

[0028] In one embodiment, the internal electrode layer may contain 0.01 at% or more and 5 at% or less of sub-elements with respect to 100 at% of the main component metal element. When the internal electrode layer contains two or more elements as sub-elements, the total concentration of the two or more sub-elements is 0.01 at% or more and 5 at% or less.

[0029] The explanation regarding the components of the first internal electrode layers 21 also applies to the components of the second internal electrode layers 22.

[0030] In one embodiment, the film thickness (dimension in the T-axis direction) of the first internal electrode layer 21 is 0.1 μm or more and 2 μm or less. In one embodiment, the film thickness of the first internal electrode layer 21 is desirably 0.4 μm or less. The explanation regarding the film thickness of the first internal electrode layer 21 also applies to the second internal electrode layer 22.

[0031] 1-2-2 Electrode and non-electrode parts The internal electrode layer will be further described with reference to FIG. 3. FIG. 3 is an enlarged cross-sectional view showing an area A of the cross section of the main body 10 shown in FIG. 2. Area A is an area with a dimension L0 in the L-axis direction of about 50 μm. As shown in FIG. 3, the first internal electrode layer 21 includes a first electrode portion 21a containing a main component metal element and a plurality of first non-electrode portions 21b surrounded by the first electrode portion 21a. The first electrode portion 21a includes a sintered body of the main component metal element. Therefore, the first electrode portion 21a has high conductivity. As shown in FIG. 3, the first electrode portion 21a of the first internal electrode layer 21 is observed to be arranged in a plurality of parts separated by the first non-electrode portions 21b in a cross section cut along the stacking direction (the T-axis direction in FIG. 3).

[0032] The first non-electrode portion 21b is interposed between the first electrode portions 21a adjacent to each other in the L-axis direction, and has higher insulation properties than the first electrode portions 21a. As described below, the first non-electrode portion 21b includes a secondary phase formed by solidification of a liquid phase sintering aid that flows between the first electrode portions 21a during the manufacturing process of the multilayer ceramic capacitor 1. Thus, the first non-electrode portion 21b contains a sintering aid element contained in the sintering aid. A portion of the first non-electrode portion 21b may be occupied by an oxide of a subelement, a portion of the ceramic layer 11, and / or a gap (void).

[0033] As will be described in detail later, the first internal electrode layer 21 is formed by firing an internal electrode pattern containing a main component metal element. As the sintering of the main component metal element progresses in this firing process, the shape of the sintered body of the main component metal element approaches a spherical shape. In the firing process, the sintered body of the main component metal element becomes spherical, which generates voids between adjacent sintered bodies of the main component metal element, allowing a sintering aid in liquid phase to enter the voids.

[0034] In one embodiment, the continuity rate of the internal electrode layers in the multilayer ceramic capacitor 1 is desirably 75% or more. The continuity rate of the first internal electrode layer 21 can be calculated as follows. First, the multilayer ceramic capacitor 1 is polished so that the LT surface becomes the observation surface. Next, a region A included in this observation surface is observed with a SEM (scanning electron microscope), and a region that appears bright in the SEM image due to a contrast difference is specified as the first electrode portion 21a. Then, the length of this first electrode portion 21a (in the illustrated example, the length along the L-axis direction) is measured, and the measured lengths L1, L2, ..., Ln are summed up. The value obtained by dividing the sum of the lengths of the first electrode portions 21a in this region A by the length L0 of the measurement region (i.e., (L1 + L2 + ... Ln) / L0) can be defined as the continuity rate of one first internal electrode layer 21. The main body 10 includes a plurality of first internal electrode layers 21, and the continuity rate can vary depending on which layer is focused on among the plurality of first internal electrode layers 21. Therefore, ten different first internal electrode layers 21 are selected, and the average of the continuity rates calculated for each of the selected first internal electrode layers 21 can be defined as the continuity rate of the first internal electrode layers 21 in the multilayer ceramic capacitor 1.

[0035] Like the first internal electrode layer 21, the second internal electrode layer 22 can also include a plurality of electrode parts containing a main component metal element and a non-electrode part existing between the electrode parts. Specifically, as shown in FIG. 3, the second internal electrode layer 22 includes a plurality of second electrode parts 22a containing a main component metal element and a second non-electrode part 22b existing between the second electrode parts 22a. The first non-electrode part 21b may include a secondary phase formed by solidifying a liquid phase sintering aid that has flowed between the first electrode parts 21a during the manufacturing process of the multilayer ceramic capacitor 1. The continuity rate of the second internal electrode layer 22 is defined in the same manner as the continuity rate of the first internal electrode layer 21. In addition, the average of the continuity rate of the first internal electrode layer 21 and the continuity rate of the second internal electrode layer 22 can be defined as the continuity rate of the internal electrode layer in the multilayer ceramic capacitor 1.

[0036] In the multilayer ceramic capacitor 1, a capacitance is generated in a region where the first electrode portion 21a of the first internal electrode layer 21 and the second electrode portion 22a of the second internal electrode layer 22 face each other in the lamination direction, i.e., in the T-axis direction in the illustrated embodiment. Conversely, the first non-electrode portion 21b and the second non-electrode portion 22b do not generate capacitance. Therefore, in order to make the multilayer ceramic capacitor 1 have a high capacity, it is desirable that the continuity rate of the internal electrode layers is high. In one aspect, the continuity rate of the internal electrode layers is 75% or more. This makes it possible to obtain a multilayer ceramic capacitor 1 having a high capacity.

[0037] The first non-electrode portion 21b is interposed between the first electrode portions 21a that generate capacitance in the multilayer ceramic capacitor 1 in the length direction of the cross section of the internal electrode layer, i.e., in the L-axis direction in the illustrated embodiment. Similarly, the second non-electrode portion 22b is interposed between the second electrode portions 22a that generate capacitance in the multilayer ceramic capacitor 1 in the length direction of the cross section of the internal electrode layer, i.e., in the L-axis direction in the illustrated embodiment. In this specification, focusing on the arrangement of the first non-electrode portion 21b relative to the first electrode portion 21a and the arrangement of the second non-electrode portion 22b relative to the second electrode portion 22a, the first non-electrode portion 21b and / or the second non-electrode portion 22b may be referred to as "between internal electrodes" or "internal electrode regions".

[0038] 1-3 Ceramic layer 11 1-3-1 Composition of ceramic layer 11 The ceramic layer 11 contains a crystal of a ceramic material represented by the chemical formula ABO3 as a main component. That is, the ceramic layer 11 contains a crystal of an oxide represented by the chemical formula ABO3 as a main phase. This oxide may have a perovskite structure. A component contained in the ceramic layer 11 at 50 wt% or more based on the total mass of the ceramic layer 11 can be regarded as the main component of the ceramic layer 11. When the ceramic layer 11 contains an oxide represented by the chemical formula ABO3 at 50 wt% or more, it can be said that the ceramic layer 11 contains an oxide represented by the chemical formula ABO3 as a main component. The ceramic layer 11 preferably contains an oxide represented by the chemical formula ABO3 at 60 wt% or more, 70 wt% or more, 80 wt% or more, or 90 wt% or more.

[0039] In the chemical formula ABO3, "A" is at least one element selected from the group consisting of Ba (barium), Sr (strontium), Ca (calcium), and Mg (magnesium). In the chemical formula ABO3, "B" is at least one element selected from the group consisting of Ti (titanium), Zr (zirconium), and Hf (hafnium). When the oxide represented by the chemical formula ABO3 has a perovskite structure, the elements "A" and "B" are located at the A site and the B site of the perovskite structure, respectively. Examples of oxides contained as a main component in the ceramic layer 11 include BaTiO3 (barium titanate), CaZrO3 (calcium zirconate), CaTiO3 (calcium titanate), SrTiO3 (strontium titanate), and MgTiO3 (magnesium titanate).

[0040] The oxide contained as the main component in the ceramic layer 11 is represented by the chemical formula Ba 1-x-y Ca x Sr y Ti 1-z Zr zO3 (0≦x≦1, 0≦y≦1, 0≦z≦1). Examples of this type of oxide include barium strontium titanate, barium calcium titanate, barium zirconate, barium titanate zirconate, calcium titanate zirconate, and barium calcium titanate zirconate.

[0041] The ceramic layer 11 may contain an additive element in addition to the oxide of the main component. In one embodiment, the additive element contained in the ceramic layer 11 is at least one element selected from the group consisting of Fe, Ni, Mo, Nb (niobium), Ta (tantalum), W, Mg, Mn (manganese), V (vanadium), and Cr. The ceramic layer 11 may contain two or more types of the additive elements.

[0042] The ceramic layer 11 may contain an oxide of a rare earth element in addition to the oxide of the main component. The oxide of the rare earth element contained in the ceramic layer 11 may be an oxide of at least one rare earth element selected from the group consisting of Y (yttrium), Sm (samarium), Eu (europium), Gd (gadolinium), Tb (terbium), Dy (dysprosium), Ho (holmium), Er (erbium), Tm (thulium), and Yb (ytterbium). The ceramic layer 11 may contain two or more types of oxides of rare earth elements.

[0043] The ceramic layer 11 may further include another type of oxide. For example, the ceramic layer 11 may include an oxide of at least one element selected from the group consisting of Co, Ni (nickel), Na (sodium), and K (potassium). The ceramic layer 11 may include two or more types of oxides of these elements.

[0044] In one embodiment, the thickness (dimension in the T-axis direction) of the ceramic layer 11 is set to 0.2 to 10 μm.

[0045] 1-3-2 Crystal grains The ceramic layer 11 includes a plurality of crystal grains of a ceramic material. That is, the ceramic layer 11 is a polycrystalline body including a plurality of crystal grains 40. At least a portion of the plurality of crystal grains has a core-shell structure. With further reference to FIG. 4, the crystal grains included in the ceramic layer 11 will be described. FIG. 4 is an enlarged cross-sectional view showing an enlarged region A of the cross section of the main body 10 shown in FIG. 2, and FIG. 4 shows a schematic cross section of one crystal grain. Region A extends from the first internal electrode layer 21 through the ceramic layer 11 to the second internal electrode layer 22.

[0046] As shown in FIG. 3, the ceramic layer 11 includes a plurality of crystal grains 40 .

[0047] In the illustrated embodiment, the crystal grain 40 has a core portion 41 and a shell portion 42. An element (e.g., a rare earth element) added to the ceramic layer 11 is dissolved in a larger amount in the shell portion 42 than in the core portion 41. The core portion 41 and the shell portion 42 are distinguished, for example, by a contrast difference in a mapping image obtained by STEM-EDS. As described above, the added elements contained in the ceramic layer 11 are dissolved in a larger amount in the shell portion 42 than in the core portion 41, so that a region in the observation field where a large amount of these added elements are detected can be identified as the shell portion 42.

[0048] Adjacent crystal grains 40 are separated by grain boundaries 45. The crystal grains 40 have atoms regularly arranged, and grain boundaries 45 are interposed between adjacent ones of the crystal grains 40. The number of crystal grains 40 interposed between the first internal electrode layer 21 and the second internal electrode layer 22 adjacent to the first internal electrode layer 21 may be three or less, as shown in the figure. By reducing the number of crystal grains 40 interposed between the first internal electrode layer 21 and the second internal electrode layer 22, a high capacitance can be obtained. A first interface layer 47 is provided between the first internal electrode layer 21 and the crystal grains 40 adjacent to the first internal electrode layer 21. A second interface layer 48 is provided between the second internal electrode layer 22 and the crystal grains 40 adjacent to the second internal electrode layer 22.

[0049] In manufacturing the multilayer ceramic capacitor 1, a sintering aid is added to the ceramic green sheets, which are precursors of the ceramic layers 11, and a predetermined number of laminate units each having an internal electrode pattern containing a main component metal element such as Ni formed on the surface of the ceramic green sheets are laminated to form a green laminate, and the green laminate is fired to produce the multilayer ceramic capacitor 1. By firing the green laminate, the ceramic green sheets become the ceramic layers 11, and the internal electrode patterns become the first internal electrode layer 21 and the second internal electrode layer 22. During firing, the sintering aid becomes a liquid phase, and elements of the raw material powder contained in the ceramic green sheets are dissolved into the liquid phase, and the dissolved elements are precipitated on the crystals, thereby promoting the growth of the crystal grains 40. In addition, the rearrangement of the crystal grains 40 is promoted in the liquid phase, thereby densifying the ceramic layers 11. As the sintering aid, a low-melting glass can be used. The low-melting glass used as the sintering aid can contain, for example, SiO2, B2O3, and a mixture thereof. As the sintering aid, various low-melting glass can be used. Examples of low-melting glass that can be used as a sintering aid include borosilicate glass and phosphate glass. B2O3 or P2O5 powder or a mixture powder of these may be used as a sintering aid. In this specification, elements other than oxygen contained in the sintering aid may be called "sintering aid elements." For example, when a low-melting glass containing SiO2 is used as a sintering aid, Si is the sintering aid element. Examples of sintering aid elements include Si, B, and P.

[0050] By adding a sufficient amount of sintering aid to the ceramic green sheet, the sintering of the raw material powder contained in the ceramic green sheet is promoted, even when the sheet is fired at a low temperature (e.g., 1100°C or lower), and the densification of the crystal grains 40 is promoted.

[0051] The grain boundary 45, the first interface layer 47, and the second interface layer 48 contain a secondary phase formed by solidification of a sintering aid that became liquid during firing, and an oxide of an element contained in the main phase oxide (main component oxide) that constitutes the ceramic layer 11. For example, when the main component oxide of the ceramic layer 11 is barium titanate, the grain boundary 45, the first interface layer 47, and the second interface layer 48 contain a secondary phase, an oxide of titanium (TiO2), and an oxide of barium (BaO).

[0052] 1-4 First intermediate layer 51 and second intermediate layer 52 In the illustrated embodiment, a first intermediate layer 51 is provided between the ceramic layer 11 and the first internal electrode layer 21. A second intermediate layer 52 is provided between the ceramic layer 11 and the second internal electrode layer 22. The first intermediate layer 51 contains the same element as the sub-element contained in the first internal electrode layer 21. The second intermediate layer 52 contains the same element as the sub-element contained in the second internal electrode layer 22. That is, the first intermediate layer 51 and the second intermediate layer 52 contain one element or two or more elements selected from the group consisting of As, Au, Co, Cr, Cu, Fe, In, Ir, Mg, Os, Pd, Pt, Re, Rh, Ru, Se, Sn, Ge, Te, W, Y, Ag, and Mo. The concentration of the sub-element in the first intermediate layer 51 is higher than the concentration of the sub-element in the first internal electrode layer 21. In other words, the sub-element is concentrated in the first intermediate layer 51. For example, the first intermediate layer 51 contains the sub-element at a concentration 1.2 times or more higher than the concentration of the sub-element in the first internal electrode layer 21. Similarly, the concentration of the sub-element in the second intermediate layer 52 is higher than the concentration of the sub-element in the second internal electrode layer 22. In other words, the sub-element is concentrated in the second intermediate layer 52. For example, the second intermediate layer 52 contains the sub-element at a concentration 1.2 times or more higher than the concentration of the sub-element in the second internal electrode layer 22.

[0053] The first intermediate layer 51 containing the concentrated sub-element can increase the Schottky barrier formed between the ceramic layer 11 and the first internal electrode layer 21. Similarly, the second intermediate layer 52 containing the concentrated sub-element can increase the Schottky barrier formed between the ceramic layer 11 and the second internal electrode layer 22. By increasing the Schottky barrier formed between the ceramic layer 11 and the first internal electrode layer 21, it is possible to suppress the occurrence of insulation deterioration caused by the accumulation of oxygen defects near the first internal electrode layer 21 and / or the second internal electrode layer 22, and as a result, it is possible to improve the insulation reliability of the multilayer ceramic capacitor 1. In other words, it is possible to extend the life of the multilayer ceramic capacitor 1.

[0054] The thickness of the first intermediate layer 51 (dimension in the T-axis direction) is, for example, 0.2 nm or more and 3.0 nm or less. The lower limit of the thickness of the first intermediate layer 51 may be 0.3 nm, 0.4 nm, or 0.5 nm. The upper limit of the thickness of the first intermediate layer 51 may be 2.0 nm, 1.5 nm, or 1.3 nm. The thickness of the second intermediate layer 52 may be approximately the same as the thickness of the first intermediate layer 51.

[0055] In the illustrated embodiment, the main body 10 includes a first intermediate layer 51 and a second intermediate layer 52. Therefore, the Schottky barrier can be increased in both sections between the ceramic layer 11 and the first internal electrode layer 21 and between the ceramic layer 11 and the second internal electrode layer 22. In one embodiment, the main body 10 includes the first intermediate layer 51 but does not necessarily include the second intermediate layer 52. In this case, the Schottky barrier between the ceramic layer 11 and the first internal electrode layer 21 can be increased. In one embodiment, the main body 10 includes the second intermediate layer 52 but does not necessarily include the first intermediate layer 51. In this case, the Schottky barrier between the ceramic layer 11 and the second internal electrode layer 22 can be increased.

[0056] According to the results of the inventor's verification, the first intermediate layer 51 and the second intermediate layer 52 have poor wettability with a liquid-phase sintering aid containing any one of Si, B, and P as a sintering aid element, so that the sintering aid that becomes liquid during firing does not remain between the first interface layer 47 between the ceramic layer 11 and the first internal electrode layer 21 and the second interface layer 48 between the ceramic layer 11 and the second internal electrode layer 22, but is easily discharged between the internal electrodes (i.e., non-electrode parts (e.g., first non-electrode part 21b, second non-electrode part 22b) formed in the internal electrode layer). In this way, by forming an intermediate layer in the internal electrode layer, it is possible to promote the discharge of the sintering aid from the ceramic green sheet to between the internal electrodes.

[0057] The first intermediate layer 51 can be distinguished from the adjacent first internal electrode layer 21 and ceramic layer 11 by observing a cross section of the main body 10 using high-angle annular dark-field-scanning transmission electron microscopy (HAADF-STEM). The first intermediate layer 51 is observed as a region of relatively high brightness between the ceramic layer 11 and the first internal electrode layer 21, which appears brighter than the ceramic layer 11. Similarly, the second intermediate layer 52 is observed as a region of relatively high brightness between the ceramic layer 11 and the second internal electrode layer 22.

[0058] The multilayer ceramic capacitor 1 may not include either or both of the first intermediate layer 51 and the second intermediate layer 52. In some embodiments, the first intermediate layer 51 and the second intermediate layer 52 are not essential components, but since they promote the discharge of the liquid phase sintering aid from the ceramic layers 11 to between the internal electrodes, it is desirable for the multilayer ceramic capacitor 1 to include the first intermediate layer 51 and the second intermediate layer 52.

[0059] 1-5 First external electrode 31 and second external electrode 32 In one embodiment, the first external electrode 31 and the second external electrode 32 are formed by applying a conductive paste to the main body 10 and heating the conductive paste. The conductive paste may include at least one material selected from the group consisting of Ag, Pd, Au, Pt, Ni, Sn, Cu, W, Ti, and alloys thereof.

[0060] 1-6 Concentration of sintering aid elements Next, we will explain the concentration of the sintering aid element contained in the multilayer ceramic capacitor 1. As described above, the sintering aid is added to the ceramic green sheets when manufacturing the multilayer ceramic capacitor 1. The sintering aid becomes liquid during firing and flows within the laminate, so the sintering aid element is contained in different concentrations in different parts of the multilayer ceramic capacitor 1.

[0061] 1-6-1 First concentration between internal electrodes First, the concentration of the sintering aid element between the internal electrodes will be described by taking the concentration of the sintering aid element contained in the first non-electrode portion 21b as an example. As described above, the first non-electrode portion 21b of the first internal electrode layer 21 contains a secondary phase generated by solidifying a sintering aid in a liquid phase. The first non-electrode portion 21b contains the sintering aid element at a first concentration. In this specification, unless otherwise specified or unless otherwise interpreted in the context, the first concentration of the sintering aid element means the atomic ratio (at%) of the sintering aid element when the element (e.g., Ti element) that enters the B site of the main phase of the ceramic layer 11 in the observation area in the first non-electrode portion 21b is set to 100 at%. Therefore, the first concentration is expressed by quantifying the B site element and the sintering aid element in the observation area set in the first non-electrode portion 21b, and expressing the atomic ratio of the sintering aid element to the quantified B site element of 100 at%. For example, when barium titanate is used as the main component oxide of the ceramic layer 11 and low-melting point glass containing SiO2 is used as a sintering aid, the atomic ratio of Si elements to 100 at% Ti elements contained in the first internal electrode layer 21 is set to a first concentration representing the concentration of the sintering aid element in the first internal electrode layer 21.

[0062] The first non-electrode portion 21b may contain not only a secondary phase formed by solidification of the sintering aid, but also oxides of subelements. In addition, when Ba or Ti is dissolved in the sintering aid discharged to the first non-electrode portion 21b, oxides of Ba or Ti may also be present in the first non-electrode portion 21b. For this reason, the concentration of the sintering aid element in the first non-electrode portion 21b may vary depending on the position of the observation area. Therefore, instead of setting one observation area in one first non-electrode portion 21b, ten observation areas are set evenly distributed in the first non-electrode portion 21b, and the average of the concentrations of the sintering aid element measured in each of the ten observation areas is set as the first concentration, thereby making it possible to level the quantitative results of the sintering aid concentration. When the first internal electrode layer 21 has a plurality of first non-electrode portions 21b, the average of the first concentrations of the sintering aid element measured in each of the plurality of first non-electrode portions 21b can be set as the first concentration in the first non-electrode portion 21b of the first internal electrode layer 21.

[0063] 1-6-2 Second concentration in the first interface layer 47 During firing of the green laminate, the sintering aid in the liquid phase also spreads to the interface between the internal electrode layer and the ceramic layer 11. The first interface layer 47 contains a secondary phase generated by solidifying the sintering aid that spreads to the interface between the internal electrode layer and the ceramic layer 11. The first interface layer 47 contains the sintering aid element at a second concentration. The second concentration is expressed by quantifying the B-site element and the sintering aid element in the observation area included in the first interface layer 47, and expressing the atomic ratio of the sintering aid element to the quantified B-site element of 100 at%. Ten observation areas are set in the first interface layer 47 so as to be evenly distributed in the L-axis direction, and the average of the concentrations of the sintering aid element measured in each of the ten observation areas can be regarded as the second concentration.

[0064] 1-6-3 Third concentration at grain boundary 45 In the ceramic layer 11, the grain boundary 45 contains a secondary phase produced by solidification of a liquid phase sintering aid. The grain boundary 45 contains the sintering aid element at a third concentration. The third concentration is expressed by quantifying the B-site element and the sintering aid element in an observation region included in the grain boundary 45, and expressing the third concentration as the atomic ratio of the sintering aid element to the quantified B-site element (100 at%). Ten observation regions are set evenly distributed within the grain boundary 45, and the average of the concentrations of the sintering aid element measured in each of the ten observation regions can be regarded as the third concentration.

[0065] 1-6-4 Example of quantification method for first concentration to third concentration The concentrations (first to third concentrations) of the sintering aid elements contained in the multilayer ceramic capacitor 1 can be determined by the following procedure.

[0066] First, an analysis sample sliced ​​to a thickness of about 30 to 80 nm is extracted from the multilayer ceramic capacitor 1 using a focused ion beam device (FIB). As the focused ion beam device, for example, Helios G4UC manufactured by Thermo Fisher Scientific Co., Ltd. can be used. The analysis sample is extracted from the multilayer ceramic capacitor 1 by a lift-out method, for example, by setting the acceleration voltage of the focused ion beam device to 5 to 30 kV.

[0067] Next, the sliced ​​analysis sample is placed in a transmission electron microscope (TEM) equipped with an energy dispersive X-ray spectrometer (EDS), and an observation area is set on the observation surface of the analysis sample. The observation surface of the analysis sample can be a surface (LT surface) parallel to the cross section of the main body 10 shown in FIG. 3. When observing the analysis sample, the multilayer ceramic capacitor 1 may be sliced ​​along the WT surface so that the WT surface can be used as the observation surface. A JEM-ARM200F NEOARM manufactured by JEOL Ltd. can be used as the TEM.

[0068] When the first concentration is obtained, the observation area is set in the first non-electrode portion 21b on the observation surface. When the second concentration is obtained, the observation area is set so as to include the first interface layer 47. When the third concentration is obtained, the observation area is set in the grain boundary 45. The observation area is, for example, a square area of ​​15 to 50 nm on each side. When the first concentration is obtained, the observation area is set so that the entire observation area is within the first non-electrode portion 21b. Since the observation area set for measuring the first concentration is entirely within the first non-electrode portion 21b, the average of the measured values ​​of the concentration at each spot within the observation area can be taken as the first concentration. When the second concentration is obtained, the observation area is set so that two opposing sides of the four sides that define the outline of the rectangular observation area intersect with the first interface layer 47. Since the observation area set for measuring the second concentration includes areas other than the first interface layer 47 (for example, crystal grains 40 and internal electrode layers), a scan line is set along the first interface layer 47 intersecting between two opposing sides of the four sides that define the outer shape of the observation area, and the measured values ​​of the concentration are reconstructed along this scan line, and the average of the concentrations reconstructed on this scan line can be set as the second concentration. When the third concentration is to be obtained, the observation area is set so as to include the grain boundary 45 that separates the adjacent crystal grains 40 at the center of the observation area. Depending on the size of the grain boundary 45, the observation area set for measuring the third concentration can be entirely placed within the grain boundary 45. When the entire observation area is within the grain boundary 45, the average of the measured values ​​of the concentration at each spot within the observation area can be set as the third concentration. When the grain boundary 45 is small, the observation area may include areas other than the grain boundary 45 (for example, crystal grains 40). When the observation area includes areas other than the grain boundary 45, the average of the measured values ​​of the concentration at the spots within the grain boundary 45 located near the center of the observation area can be set as the third concentration.

[0069] Next, STEM-EDS analysis is performed on this observation area to obtain mapping data of quantitative elements contained in the analysis sample. In the EDS measurement, the acceleration voltage can be set to 200 kV, the spot size to 6c, the convergence aperture to 2-1, and the process time to T4. The intensity of the K-line of Ti can be used for the quantitative evaluation of Ti. The intensity of the K-line of the sintering aid element (e.g., Si) can be used for the quantitative evaluation of the sintering aid element (e.g., Si). In the quantitative evaluation, the content of each element in the observation area can be calculated by applying a correction (e.g., Zaf correction) that takes into account the atomic number effect, the absorption effect, and the fluorescence excitation effect to the spectrum of the K-line of Ti and the K-line of the sintering aid element. In the quantitative evaluation, the concentration of each element can be calculated by applying a correction to the spectrum of each element using the proportionality coefficient (K factor) used in the Cliff-Flow-Limer method. In addition to the correction used in the Cliff-Flow-Limer method, a correction that takes into account the absorption effect of the sample can be applied to calculate the concentration of each element. The absorption effect of a sample can be determined by determining the thickness and density of the sample. The thickness of the sample can be determined, for example, by acquiring a convergent-beam electron diffraction (CBED) pattern under two-beam excitation conditions and analyzing the rocking curve observed on a diffraction disk. The density of the sample can be, for example, 6.02 g / cm3, which is the density of barium titanate. In the EDS measurement, it is desirable to perform the measurement so that the Ti K line can be obtained with sufficient intensity, for example, the intensity at the Ti K line peak is 10,000 counts or more.

[0070] 1-6-5 Comparison of 1st, 2nd, and 3rd concentrations In one aspect, the first concentration indicating the concentration of the sintering aid element in the first non-electrode portion 21b is higher than the second concentration indicating the concentration of the sintering aid element in the first interface layer 47. According to the verification by the present inventor, in a conventional multilayer ceramic capacitor that does not have a mechanism for promoting the discharge of the liquid phase sintering aid from the ceramic layer to between the internal electrodes, the sintering aid is likely to accumulate at the interface between the ceramic layer and the internal electrode layer during firing, and the sintering aid accumulated at this interface is likely to solidify, forming a low dielectric constant layer containing a high concentration of the sintering aid element with a low relative dielectric constant between the ceramic layer and the internal electrode layer. When a low dielectric constant layer is formed at the interface between the ceramic layer and the internal electrode layer, the electrostatic capacitance of the multilayer ceramic capacitor is greatly reduced. In contrast, in the multilayer ceramic capacitor 1 according to the embodiment of the present invention, the first intermediate layer 51, which has poor wettability with the liquid phase sintering aid, promotes the discharge of the liquid phase sintering aid to the first non-electrode portion 21b during firing, so that a low dielectric constant layer with a high concentration of the sintering aid element is not formed between the ceramic layer 11 and the first internal electrode layer 21. In the multilayer ceramic capacitor 1, by confirming that the second concentration indicating the concentration of the sintering aid element in the first interface layer 47 is lower than the first concentration indicating the concentration of the sintering aid element in the first non-electrode portion 21b, it can be confirmed that a low dielectric constant layer containing a high concentration of the sintering aid element is not formed between the ceramic layer 11 and the first internal electrode layer 21.

[0071] In one embodiment, the first concentration can be 10 at% or more. Even if a sufficient amount of sintering aid is added to the ceramic green sheets to perform low-temperature sintering (for example, sintering at a densification temperature of less than 1050°C), if the first concentration is 10 at% or more, the sintering aid is sufficiently discharged from the ceramic layers 11 to between the internal electrode layers, so that the ceramic layers 11 can be densified by low-temperature sintering while suppressing a decrease in the capacitance of the multilayer ceramic capacitor 1.

[0072] In one embodiment, the second concentration can be 0.5 at% or less. If the second concentration indicating the concentration of the sintering aid element in the first interface layer 47 is 0.5 at% or less, a low dielectric constant layer that leads to a decrease in the capacitance of the multilayer ceramic capacitor 1 is not formed between the ceramic layer 11 and the first internal electrode layer 21. By preventing the formation of a low dielectric constant layer at the interface between the ceramic layer 11 and the first internal electrode layer 21, the decrease in the capacitance of the multilayer ceramic capacitor 1 can be suppressed.

[0073] In one embodiment, a third concentration indicating the concentration of the sintering aid element in the grain boundary 45 is lower than a first concentration indicating the concentration of the sintering aid element in the first non-electrode portion 21b. By making the third concentration lower than the first concentration, it is possible to reduce the amount of the sintering aid element remaining in the ceramic layer 11 after firing, so that it is possible to densify the ceramic layer 11 by low-temperature sintering while suppressing a decrease in the capacitance of the multilayer ceramic capacitor 1.

[0074] In one embodiment, the third concentration indicating the concentration of the sintering aid element in the grain boundary 45 is higher than the second concentration indicating the concentration of the sintering aid element in the first interface layer 47. In other words, the second concentration is lower than the third concentration. As described above, when a low dielectric constant layer having a low dielectric constant is formed between the ceramic layer and the internal electrode layer, the capacitance of the multilayer ceramic capacitor is significantly reduced. By making the second concentration lower than the third concentration, it is possible to prevent the sintering aid element having a low dielectric constant from segregating in layers in the region between the ceramic layer 11 and the first internal electrode layer 21, and thus it is possible to suppress the reduction in the capacitance of the multilayer ceramic capacitor 1.

[0075] In one embodiment, the third concentration can be 0.5 at% or less. By setting the third concentration to 0.5 at% or less, the amount of sintering aid elements remaining in the ceramic layers 11 after firing can be reduced, so that the ceramic layers 11 can be densified by low-temperature sintering while suppressing a decrease in the capacitance of the multilayer ceramic capacitor 1.

[0076] In this specification, the description of the first concentration indicating the concentration of the sintering aid element in the first non-electrode portion 21b of the first internal electrode layer 21 also applies to the concentration of the sintering aid element in the second non-electrode portion 22b of the second internal electrode layer 22, and the description of the second concentration indicating the concentration of the sintering aid element in the first interface layer 47 also applies to the concentration of the sintering aid element in the second interface layer 48. In addition, in this specification, the description of the relationship between the first concentration and the second concentration also applies to the relationship between the concentration of the sintering aid element in the second non-electrode portion 22b of the second internal electrode layer 22 and the concentration of the sintering aid element in the second interface layer 48. For example, the concentration of the sintering aid element in the second non-electrode portion 22b of the second internal electrode layer 22 (corresponding to the first concentration) is higher than the concentration of the sintering aid element in the second interface layer 48 (corresponding to the second concentration). As a result, no low dielectric constant layer that would lead to a decrease in the capacitance of the multilayer ceramic capacitor 1 is formed between the ceramic layers 11 and the second internal electrode layers 22.

[0077] 2. Manufacturing method of multilayer ceramic capacitor 1 Next, an example of a method for manufacturing the multilayer ceramic capacitor 1 will be described with reference to Figures 5, 6a, and 6b. Figure 5 is a flow diagram showing the flow of a method for manufacturing a multilayer ceramic capacitor according to one embodiment of the present invention.

[0078] Briefly explaining the manufacturing method shown in FIG. 5, in step S1, a green laminate which is a precursor of the main body 10 is formed. This green laminate includes a ceramic green sheet which is a precursor of the ceramic layer 11, and an internal conductor pattern which is a precursor of each of the first internal electrode layer 21 and the second internal electrode layer 22. The green laminate may be formed by alternately laminating a ceramic green sheet on which an internal conductor pattern which is a precursor of the first internal electrode layer 21 is provided on the surface and a ceramic green sheet on which an internal conductor pattern which is a precursor of the second internal electrode layer 22 is provided on the surface. The ceramic green sheet contains a sintering aid. The internal conductor pattern contains sub-elements such as Au and Fe in addition to the main component metal element. Next, in step S2, the green laminate formed in step S1 is heated in a firing furnace to fire the ceramic green sheet and the internal electrode pattern (first heat treatment), and then, in step S3, the fired laminate is held at a predetermined keep temperature for a predetermined time (second heat treatment), and finally, in step S4, the firing furnace is cooled to obtain a multilayer ceramic capacitor 1.

[0079] Each step shown in FIG. 5 will be described in more detail below. First, in step S1, a binder such as polyvinyl butyral (PVB) resin, an organic solvent such as ethanol or toluene, a plasticizer, and a sintering aid are added to the ceramic powder and wet mixed to obtain a slurry. As the sintering aid, for example, low-melting glass containing SiO2, B2O3, and a mixture thereof can be used. Examples of low-melting glass include borosilicate glass and phosphate glass. B2O3 powder or P2O5 powder may be used as the sintering aid. Then, this slurry is applied onto a substrate film by, for example, a die coater method or a doctor blade method, and the slurry applied onto the substrate film is dried to obtain a ceramic green sheet. The ceramic green sheet is a precursor of the ceramic layer 11.

[0080] The ceramic powder, which is the raw material powder of the ceramic green sheet, is, for example, barium titanate powder. The barium titanate powder is synthesized by reacting a titanium raw material such as titanium dioxide with a barium raw material such as barium carbonate by a known method such as a solid-phase method, a sol-gel method, or a hydrothermal method.

[0081] Next, the internal electrode patterns are formed on the plurality of ceramic green sheets formed as described above. The internal electrode patterns are formed, for example, by printing the internal electrode paste on the ceramic green sheets by a known printing method such as screen printing. When the internal electrode patterns are formed by screen printing, the internal electrode paste is manufactured by kneading metal powder, binder resin, and solvent with a three-roll mill. That is, the internal electrode paste is a paste in which metal powder is dispersed in binder resin. The metal powder contained in the internal electrode paste may be a mixed powder obtained by mixing powder of a main component metal element such as Ni, Cu, Sn, etc., which is the main component of the first internal electrode layer 21 and the second internal electrode layer 22, with powder containing a sub-element. The mixed powder is generated by mixing the main component metal powder with the sub-element powder so that the content ratio of the sub-element to 100 at% of the main component metal element is in the range of 0.01 to 5 at%. When the multilayer ceramic capacitor 1 does not include the first intermediate layer 51 and the second intermediate layer 52, the sub-element powder may not be added. As the organic binder for the internal electrode paste, a cellulose-based resin such as ethyl cellulose or an acrylic resin such as butyl methacrylate can be used. The internal electrode pattern formed on some of the ceramic green sheets is a precursor of the first internal electrode layer 21, and the internal electrode pattern formed on the other ceramic green sheets is a precursor of the second internal electrode layer 22.

[0082] The internal electrode pattern may be formed on the ceramic green sheet by a sputtering method. The method of forming the internal electrode pattern is not limited to the method specifically described in this specification. The internal electrode pattern may be formed by various known methods, such as vacuum deposition, PLD (pulsed laser deposition), MO-CVD (metal organic chemical vapor deposition), MOD (metal organic decomposition), or CSD (chemical solution deposition).

[0083] In this manner, a laminate unit having a ceramic green sheet and an internal electrode pattern formed on the surface of the ceramic green sheet is obtained. A predetermined number of such laminate units are laminated and thermocompression bonded to obtain a green laminate. Green sheets without an internal electrode pattern may be laminated on the top and bottom layers of the green laminate.

[0084] Next, the green laminate is singulated to obtain a chip-shaped green laminate that serves as a precursor of the main body 10. The chip-shaped green laminate may be subjected to a degreasing treatment. The degreasing treatment may be performed in an N2 atmosphere. Furthermore, a metal paste that serves as the base electrode layers of the first external electrode 31 and the second external electrode 32 may be applied by a dipping method to the green laminate that has been subjected to the degreasing treatment.

[0085] FIG. 6a is a schematic enlarged view of a cross section of a chip-shaped green laminate cut along the lamination direction. As shown in FIG. 6a, in the green laminate 110, an internal electrode pattern 121, which is a precursor of the first internal electrode layer 21, is provided on one surface in the lamination direction of a ceramic green sheet 111, and an internal electrode pattern 122, which is a precursor of the second internal electrode layer 22, is provided on the other surface in the lamination direction of the ceramic green sheet 111. The ceramic green sheet 111 includes a ceramic powder 61 and a sintering aid powder 62. The ceramic powder 61 is, for example, a barium titanate powder. The sintering aid powder 62 is, for example, a low-melting-point glass powder containing SiO2. The internal electrode patterns 121 and 122 include a main component metal element powder 71 and a sub-element powder 72. The main component metal element powder 71 is, for example, a Ni powder. The sub-element powder 72 is, for example, a Au powder. When the multilayer ceramic capacitor 1 does not include the first intermediate layer 51 and the second intermediate layer 52, the addition of the sub-element powder can be omitted.

[0086] Next, in step S2, the chip-shaped green laminate 110 produced in step S1 is placed in a firing furnace, and the green laminate 110 is subjected to a heat treatment (first heat treatment) in the firing furnace according to a predetermined temperature profile. By this first heat treatment, the ceramic green sheets 111 in the green laminate 110 are fired to become the ceramic layers 11, the internal electrode patterns 121 are fired to become the first internal electrode layers 21, and the internal electrode patterns 122 are fired to become the second internal electrode layers 22.

[0087] An example of the temperature profile of the first heat treatment will be described. The temperature in the sintering furnace is increased from room temperature to the intermediate temperature at 200 to 300°C / h. The intermediate temperature is set to a temperature slightly lower than the sintering temperature of the main component metal element. When the main component metal element is Ni, the intermediate temperature is set to about 500 to 700°C. An example of the intermediate temperature is 600°C. Next, the temperature is increased at a high heating rate from this intermediate temperature to the top sintering temperature. The top sintering temperature is, for example, 1000 to 1050°C. An example of the top sintering temperature is 1040°C. The heating rate is, for example, 20000 to 40000°C / h. An example of the heating rate is 30000°C / h. The first holding time at the top sintering temperature is within 10 seconds to prevent excessive sintering of the internal electrode layer. Cooling may be started immediately after the top sintering temperature is reached.

[0088] In the first heat treatment, the green laminate 110 is heated to a top firing temperature, and the green laminate 110 is fired to become the main body 10. Fig. 6b is an enlarged schematic cross-sectional view of the main body 10 obtained by heating the green laminate 110 to a top firing temperature and holding the green laminate 110 at the top firing temperature for a predetermined first holding time. Fig. 6b shows the main body 10 before it is cooled after being heated to the top firing temperature.

[0089] In the main body 10 shown in FIG. 6b, the ceramic powder 61 in the green laminate 110 is sintered by the first heat treatment in step S2 to form crystal grains 40 having a core portion 41 and a shell portion 42. When the ceramic powder 61 contains an additive element such as a rare earth element, the additive element diffuses to the shell portion 42 in the first heat treatment. Therefore, the additive element in the ceramic powder 61 is contained in a higher concentration in the shell portion 42 than in the core portion 41. In the ceramic layer 11, the crystal grains 40 are densely arranged. The adjacent crystal grains 40 are separated by grain boundaries 45. During the firing process, the sintering additive powder 62 in the ceramic green sheet 111 exists as a liquid phase component 80. In FIG. 6b, the grain boundaries 45 are filled with the liquid phase component 80.

[0090] In the first heat treatment in step S2, the main component metal elements in the internal electrode patterns 121 and 122 are also sintered, so that the first internal electrode layer 21 and the second internal electrode layer 22 contain sintered bodies of the main component metal elements. A part of the main component metal elements becomes spherical as the sintering proceeds, and the first internal electrode layer 21 and the second internal electrode layer 22 become partially discontinuous. In the illustrated embodiment, the main component metal elements of a part of the first internal electrode layer 21 become spherical, and a first non-electrode portion 21b in which no or almost no sintered body of the main component metal element exists is formed between the first electrode portions 21a containing the sintered body of the main component metal element. In the first heat treatment, the auxiliary elements are thermally diffused toward the interface with the ceramic green sheet in parallel with the sintering of the main component metal element. As a result, a first intermediate layer 51 containing the sub-element at a higher concentration than the first internal electrode layer 21 is formed on the surface of the first internal electrode layer 21, and a second intermediate layer 52 containing the sub-element at a higher concentration than the second internal electrode layer 22 is formed on the surface of the second internal electrode layer 22.

[0091] The liquid phase component 80 formed by melting the sintering aid powder in the first heat treatment spreads over the surface of the ceramic powder 61, promoting the sintering of the ceramic powder 61. In the main body 10, the liquid phase component 80 spreads over the surface of the crystal grains formed by sintering the ceramic powder 61, so that the grain boundaries 45 of the main body 10 are filled with the liquid phase component 80, as shown in FIG. 6b. Elements contained in the ceramic powder 61 (Ba and Ti in the case where the ceramic powder is barium titanate powder) are dissolved in the liquid phase component 80. In the firing process, the elements dissolved in the liquid phase component 80 are precipitated on the crystal surface, and thus the growth of the crystal grains 40 progresses. In addition, the rearrangement of the crystal grains 40 progresses in the liquid phase component 80, and thus the densification of the crystal grains 40 progresses.

[0092] The liquid phase component 80 spreads from the grain boundary 45 through the first interface layer 47 to between the internal electrodes (in the first non-electrode portion 21b of the first internal electrode layer 21 in the illustrated example). The first non-electrode portion 21b may be entirely filled with the liquid phase component 80, or only a part of the first non-electrode portion 21b may be filled with the liquid phase component 80 as shown in FIG. 6b. When the second non-electrode portion 22b is formed in the second internal electrode layer 22, the liquid phase component 80 may spread to the second non-electrode portion 22b through the second interface layer 48. Since the first intermediate layer 51 and the second intermediate layer 52 have poor wettability with the liquid phase component 80, the liquid phase component 80 does not remain in the first interface layer 47 and the second interface layer 48, but is discharged to the first non-electrode portion 21b and the second non-electrode portion 22b.

[0093] In the first heat treatment in step S2, the laminate is held at the firing top temperature for a first holding time (10 seconds in the above example), and then in the second heat treatment in step S3, the inside of the firing furnace is cooled to a keeping temperature lower than the firing top temperature, and the fired laminate is held at this keeping temperature for a second holding time. The keeping temperature is set to a temperature 50 to 150°C lower than the firing top temperature. The keeping temperature can be, for example, a temperature 100°C lower than the firing top temperature. The second holding time can be longer than the first holding time. The second holding time can be 1 to 3 minutes. During the holding at this keeping temperature, Ba and Ti contained in the liquid phase component 80 of the grain boundary 45 are precipitated on the surface of the crystal grain 40, causing the crystal grain 40 to grow further. Due to the growth of the crystal grains 40, the liquid phase component 80 in the grain boundary 45 is pushed out from the grain boundary 45 toward the first interface layer 47 and the second interface layer 48, and is further discharged from the first interface layer 47 and the second interface layer 48 to the first non-electrode portion 21b and the second non-electrode portion 22b. Therefore, in the second heat treatment in step S3, the main phase components (Ba and Ti) dissolved in the liquid phase component 80 are precipitated, so that the content ratio of the sintering aid element to the element of the main phase component becomes high in the liquid phase component 80, and the liquid phase component 80 with the high ratio of the sintering aid element flows into the first non-electrode portion 21b and the second non-electrode portion 22b. If a part of the first non-electrode portion 21b of the first internal electrode layer 21 is a void at the start of step S3, the liquid phase component 80 can also be poured into this void while the main body 10 is held at the keep temperature in step S3. In this manner, in the second heat treatment in step S3, the liquid phase component 80 with a high content ratio of the sintering aid elements can be expelled from the ceramic layers 11, so that the sintering aid elements with low dielectric constant contained in the ceramic layers 11 can be efficiently expelled, thereby improving the capacitance of the multilayer ceramic capacitor 1.

[0094] Next, in step S3, the laminate is held at the keep temperature for a second holding time, and then in step S4, the sintering furnace is cooled to room temperature to obtain the multilayer ceramic capacitor 1. By cooling in step S4, the liquid phase component 80 in the main body 10 is solidified to form a secondary phase. The secondary phase contains a sintering aid element. Furthermore, by cooling the liquid phase component 80, the elements of the main phase components (e.g., Ba and Ti) that have dissolved in the liquid phase component 80 are precipitated as oxides (BaO and TiO2) between the internal electrodes, in the first interface layer 47, the second interface layer 48, and in the grain boundaries 45.

[0095] 5 may be performed to manufacture the multilayer ceramic capacitor 1. For example, the multilayer ceramic capacitor 1 obtained by the second heating treatment in step S2 may be subjected to a reoxidation treatment at 600°C to 1000°C in an N2 gas atmosphere. Furthermore, a plating layer of Cu, Ni, Sn, or the like may be provided on the surfaces of the first external electrode 31 and the second external electrode 32. This plating layer may be formed by electrolytic plating or electroless plating.

[0096] In order to manufacture the multilayer ceramic capacitor 1, some of the steps shown in the flow chart of FIG. 5 can be omitted. For example, the second heat treatment in step S3 can be omitted. Even if the second heat treatment in step S3 is omitted, the liquid phase component 80 can be discharged to the first non-electrode portion 21b and the second non-electrode portion 22b. Therefore, the additional discharge of the liquid phase component 80 in the second heat treatment is not an essential step for manufacturing the multilayer ceramic capacitor 1. However, when the multilayer ceramic capacitor 1 does not include the first intermediate layer 51 and the second intermediate layer 52 (that is, when the internal electrode patterns 121 and 122 do not contain the auxiliary element powder in the above manufacturing method), the second heat treatment is performed to promote the discharge of the liquid phase component 80 to the first non-electrode portion 21b and the second non-electrode portion 22b.

[0097] 3. Working Example The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0098] 3-1 Sample preparation First, 15 kinds of samples were prepared as follows according to the manufacturing method described in FIG. 5. Specifically, first, polyvinyl butyral (PVB) resin, a solvent, a plasticizer, and a low-melting glass powder containing SiO2 as a sintering aid were added to barium titanate powder and wet mixed to obtain a slurry. The low-melting glass powder containing SiO2 was added at 5 at% relative to 100 at% Ti contained in the barium titanate powder. Then, this slurry was applied onto a substrate film, and the slurry applied onto the substrate film was dried to obtain a ceramic green sheet. Next, Ni powder, which is the main component metal element, was mixed with a sub-element powder containing the sub-elements described in Table 1 to prepare a mixed powder. However, in sample 1, no sub-elements were mixed. In sample 7, a mixed powder of Au powder and Fe powder was used as the sub-element powder. The auxiliary element powder was weighed so that the content ratio of the auxiliary element relative to Ni 100 at% was the amount listed in "Amount of auxiliary element added" in Table 1, and this weighed auxiliary element powder was mixed with Ni powder. Next, polyvinyl butyral (PVB) resin, a solvent, and a plasticizer were added to this mixed powder and wet-mixed to obtain an internal electrode slurry. Then, the internal electrode slurry was printed on a partial area of ​​the surface of the ceramic green sheet to form an internal electrode pattern on each of the ceramic green sheets, thereby forming a laminate unit. This laminate unit has ceramic green sheets and an internal electrode pattern formed on the surface of the ceramic green sheet.

[0099] [Table 1]

[0100] As shown in Table 1, the secondary element in Samples 2 and 3 is Au, and the secondary element in Sample 4 and Samples 10 to 15 is Fe. The secondary elements in the other samples are also as shown in Table 1.

[0101] Next, 500 laminated units were laminated to form a laminate, and this laminate was divided into individual pieces to obtain a chip-shaped green laminate. The chip-shaped green laminate was shaped like a 1005 (length: 1.0 mm, width: 0.5 mm, height: 0.5 mm). Next, this chip laminate was degreased in an N2 atmosphere. Next, a metal paste was applied to the molded body after the degreased process by a dipping method to form an underlayer for an external electrode on each chip laminate.

[0102] Next, the chip stack, which is the precursor of each sample obtained as described above, was placed in a sintering furnace, and the chip stack was subjected to a first heat treatment under predetermined sintering conditions according to a predetermined temperature profile. -8 The furnace was kept in a low-oxygen atmosphere of 10 ...

[0103] After the top firing temperature was maintained for 10 seconds, cooling of the inside of the firing furnace was started. When preparing samples 3 to 7, the temperature inside the firing furnace was maintained at 940°C (keep temperature), which is 100°C lower than the top firing temperature, for 2 minutes after cooling started (i.e., a second heat treatment was performed), and after maintaining at this keep temperature, the material was cooled to room temperature. For samples 1 to 2 and samples 8 to 15, the top firing temperature was maintained for 10 seconds, and the material was cooled to room temperature without maintaining at the keep temperature.

[0104] In this manner, samples of multilayer ceramic capacitors, Samples 1 to 15, were produced. In Samples 1 to 15, the ceramic green sheets were fired to form ceramic layers, and the internal electrode patterns were fired to form internal electrode layers.

[0105] Each of the samples 1 to 15 was embedded in resin, and each embedded sample was polished along a plane parallel to the lamination direction (for example, the LT plane in FIG. 2) to expose a cross section parallel to the lamination direction, and the exposed cross section was observed at a magnification of 20,000 times with a field emission scanning secondary electron microscope (FE-SEM). This observation confirmed that the crystal grains were densified in all samples. Thus, each sample was sintered at a low densification temperature of 1040°C.

[0106] 3-2 Quantitative determination of sintering aid element concentration Next, each of Samples 1 to 15 was sliced ​​using a focused ion beam (FIB) device so that the LT surface (Figure 2) was the observation surface, and a sliced ​​analysis sample with a thickness of 60 nm was extracted from each of Samples 1 to 15 by the lift-out method. A Helios G4UC manufactured by Thermo Fisher Scientific Co., Ltd. was used as the focused ion beam device. Damage that appeared on the observation surface of the sliced ​​samples was appropriately removed by Ar ion milling.

[0107] Next, the sliced ​​sample was placed in a TEM equipped with an EDS detector, and a STEM image was obtained on the observation surface of the sliced ​​sample. Based on the difference in contrast of the STEM image, the non-electrode portion in the internal electrode layer (the portion corresponding to the first non-electrode portion 21b), the interface layer existing between the ceramic layer and the internal electrode layer (the portion corresponding to the first interface layer 47), and the grain boundary between the crystal grains in the ceramic layer (the portion corresponding to the grain boundary 45) were identified. The TEM used was JEM-ARM200F NEOARM manufactured by JEOL Ltd. The EDS detector used was a dry SD100GV detector manufactured by JEOL Ltd.

[0108] First, for each sample, 10 observation regions of 30 nm square were set in the non-electrode portion (for example, the portion corresponding to the first non-electrode portion 21b) in the internal electrode layer, and the concentration of Ti element and Si element (sintering aid element) was measured by EDS for each of the 10 observation regions. During the EDS measurement, the acceleration voltage was set to 200 kV, the spot size was set to 6c, the convergence aperture was set to 2-1, and the process time was set to T4. The same measurement conditions were used for the EDS measurement in the other observation regions described below. During the quantitative evaluation, the concentration of each element was calculated by applying Zaf correction to the spectrum of the Ti K line and the Si K line. For each of the 10 observation regions, the concentration of Si (at%) was calculated when the concentration of Ti was set to 100 at%, based on the concentration of each element obtained by the EDS measurement, and the average value of the concentration of Si in the 10 observation regions is shown in the column of "Between internal electrodes (a: first concentration)" in "Sintering aid element concentration" in Table 2 below. When calculating the first concentration, the average of the concentrations measured at each spot in the observation region was used as the concentration of each element.

[0109] Next, for each sample, 10 observation areas of 30 nm square were set in the interface layer (e.g., the portion corresponding to the first interface layer 47) existing between the ceramic layer and the internal electrode layer, and the concentration of Ti element and Si element (sintering aid element) was measured by EDS for each of the 10 observation areas. For each of the 10 observation areas, a scan line was set along the first interface layer 47 intersecting with two opposing sides of the four sides defining the outline of the observation area, and the measured concentration values ​​were reconstructed along the scan line. Based on the concentration of each element obtained by averaging the EDS measured values ​​reconstructed on the scan line, the concentration of Si (at%) was calculated when the concentration of Ti was 100 at%, and the average value of the concentration of Si in the 10 observation areas is shown in the column of "Interface layer (b: second concentration)" in "Sintering aid element concentration" in Table 2 below.

[0110] Next, for each sample, ten observation regions of 30 nm square were set at the grain boundaries between crystal grains in the ceramic layer (for example, the portion corresponding to grain boundary 45), and the concentrations of Ti and Si elements (sintering aid elements) were measured by EDS for each of the ten observation regions. For each of the ten observation regions, the concentration of Si (at%) was calculated when the concentration of Ti was 100 at% based on the concentration of each element obtained by EDS measurement, and the average value of the concentration of Si in the ten observation regions is shown in the column of "Grain boundary (c: third concentration)" in "Sintering aid element concentration" in Table 2 below. Since the entire observation region was grain boundary 45, the average of the concentrations measured at each spot in the observation region was used for the calculation of the third concentration.

[0111] In Table 2, the "a / c" column shows the ratio of the first concentration to the third concentration, and the "c / b" column shows the ratio of the third concentration to the second concentration.

[0112] 3-3 Checking the middle layer Next, in the above-mentioned analysis sample, ten observation regions of 15 nm square extending from the internal electrode layer to the ceramic layer were specified, and in each of the ten observation regions, TEM-EDS analysis was performed under the conditions of an acceleration voltage of 200 kV, an electron beam diameter of 1.5 nm, and a measurement time of 2 hours. Specifically, a concentration map was obtained in each observation region, which represents the concentration of the quantitative elements (Ba, Ti, O, Ni, and the secondary element (Au in the case of sample 2)) in atomic ratio (at%), and this concentration map was reconstructed along a scanning line set to extend along the T axis from the internal electrode layer to the ceramic layer in each observation region, thereby obtaining a line profile of each quantitative element for each observation region. In the line profiles of samples 2 to 15, the peak of the secondary element appeared near the intersection of the Ba profile and the Ni profile. In the line profile of sample 1, no peak of the element corresponding to the secondary element was detected. From the results of this line analysis, it was confirmed that for samples 2 to 15, a first intermediate layer 51 containing a sub-element at a higher concentration than the first internal electrode layer 21 is formed between the ceramic layer 11 and the first internal electrode layer 21.

[0113] 3-4 Capacitance The capacitance was measured for each of Samples 1 to 14. The capacitance was measured using an LCR meter under the conditions of room temperature, a measurement voltage of 0.5 V, and a frequency of 1 kHz. 100 samples were selected for each of Samples 1 to 14, and the capacitance was calculated for each of the 100 samples. The average value of the capacitance measured for the 100 samples for each sample was calculated, and this calculated average value was used as the capacitance of the sample. The capacitance calculated in this manner is listed in the "Capacitance" column of Table 2. In addition, the "Capacitance Ratio" column of Table 2 shows the relative capacitance of each sample as a percentage based on the capacitance of Sample 1 to which no auxiliary elements are added. For example, the capacitance ratio "137%" of Sample 2 means that the calculated capacitance of Sample 2 is 137% of the capacitance of Sample 1. As for Sample 15, a short circuit occurred between the internal electrodes, so the capacitance could not be measured. In sample 15, 5.5 at% Fe was added as an auxiliary element. It is believed that a large amount of this Fe diffused into ceramic layer 11, causing abnormal grain growth in the ceramic layer and resulting in a short circuit between the internal electrodes.

[0114] [Table 2]

[0115] In Table 2, samples not included in the present invention (i.e., comparative examples) are marked with an asterisk (*) next to the sample number. Specifically, Samples 1 and 15 are comparative examples not included in the present invention.

[0116] During the preparation of sample 1, since no auxiliary element is added to the internal electrode pattern, no layer corresponding to the first intermediate layer 51 or the second intermediate layer 52 is formed on the surface of the internal electrode layer of sample 1. In addition, during the preparation process of sample 1, since the temperature is not maintained at the keep temperature after reaching the top firing temperature, the discharge of the liquid phase sintering aid from the ceramic layer 11 to the first non-electrode portion 21b of the first internal electrode layer 21 is not promoted. For this reason, it is considered that the discharge of the liquid phase sintering aid between the internal electrodes (parts corresponding to the first non-electrode portion 21b) is not sufficient in sample 1. Since the first concentration is slightly lower than the second concentration and the third concentration in sample 1, it is supported that the amount of discharge of the sintering aid between the internal electrodes is not large.

[0117] In each of Samples 2 to 14, the first concentration indicating the concentration of the sintering aid element between the internal electrodes is greater than both the second concentration and the third concentration indicating the concentration of the sintering aid element in the ceramic layer 11, which shows that more sintering aid is discharged from the ceramic layer 11 to between the internal electrodes compared to Sample 1. The capacitance of Samples 2 to 14 is improved by 10% or more compared to the capacitance of Sample 1. This improvement in capacitance is believed to be due to the fact that the content of the sintering aid element, which has a low dielectric constant, in the ceramic layer 11 is reduced by facilitating the discharge of the sintering aid from the ceramic layer 11 to between the internal electrodes.

[0118] Sintering aid elements with low relative magnetic permeability distributed in layers at the interface between the ceramic layer and the internal electrode layer significantly reduce the capacitance of the multilayer ceramic capacitor. Therefore, it is considered that the capacitance of the multilayer ceramic capacitor can be improved by promoting the discharge of the sintering aid from the interface between the ceramic layer and the internal electrode layer (the region corresponding to the first interface layer 47 and the second interface layer 48) to between the internal electrodes. In Table 2, for Samples 2 to 8 and Samples 11 to 14, the ratio (a / c) of the first concentration to the third concentration is greater than 10, so that the content of the sintering aid elements at the interface between the ceramic layer and the internal electrode layer is small. For Samples 2 to 8 and Samples 11 to 14, the capacitance is improved by 30% or more compared to Sample 1. The high improvement rate of capacitance in samples 2 to 8 and samples 11 to 14 is believed to be due to the fact that liquid phase sintering aid was discharged from the interface between the ceramic layer and the internal electrode layer to between the internal electrodes to the extent that the ratio (a / c) of the first concentration (a) to the third concentration (c) was 10 or more.

[0119] In Samples 3 to 7, which were manufactured by carrying out a temperature holding step, the ratio of the first concentration to the third concentration was greater than 30, and the capacitance was improved by 37% or more compared to Sample 1. This remarkable improvement in capacitance is believed to be due to the fact that the crystal grains in the ceramic layers further grew in the temperature holding step, causing the liquid phase component with a higher content ratio of the sintering aid element to be discharged between the internal electrodes. In this way, by carrying out a temperature holding step in which the laminate is held at a keep temperature that is lower than the top firing temperature but can promote the growth of the crystal grains 40 after the firing top temperature is reached, the decrease in capacitance due to the sintering aid can be further suppressed.

[0120] From the samples 10 to 14, it can be seen that the higher the content ratio of Fe contained in the internal electrode pattern as a sub-element, the greater the improvement in capacitance. When the content ratio of Fe is high, a layer (the first intermediate layer 51 and the second intermediate layer 52) with poor wettability with the liquid phase sintering aid is formed on the surface of the internal electrode layer, and this layer with a high content ratio of the sub-element and poor wettability with the sintering aid is thought to promote the discharge of the sintering aid from the interface between the ceramic layer and the internal electrode layer to between the internal electrodes. In this way, by increasing the amount of the sub-element added within a range where the insulation of the ceramic layer 11 can be ensured, the decrease in capacitance due to the sintering aid can be further suppressed. The upper limit of the amount of the sub-element added can be 5 at % with respect to 100 at % of the main component metal element.

[0121] Although the experimental results are omitted, it was confirmed that when As, Co, Cu, Ir, Mg, Os, Pd, Pt, Re, Rh, Ru, Se, Sn, Ge, Te, W, Y, Ag, and Mo are used as auxiliary elements in addition to Au, Fe, In, and Cr, which are added as auxiliary elements to the main component metal elements in samples 2 to 14, an intermediate layer that promotes the discharge of the liquid phase sintering aid is formed, as in samples 2 to 14 listed in Table 2.

[0122] Experimental results showing the same tendency as in Table 2 were obtained when the low-melting glass used as the sintering aid contained B2O3 instead of SiO2.

[0123] 4 Notes The dimensions, materials, and arrangements of each component described in the various embodiments above are not limited to those explicitly described in each embodiment, and each component can be modified to have any dimensions, materials, and arrangements that may fall within the scope of the present invention.

[0124] Components not explicitly described in this specification may be added to each of the above-described embodiments, and some of the components described in each embodiment may be omitted.

[0125] The designations "first," "second," "third," and the like in this specification are given to identify components, and do not necessarily limit the number, order, or content. Furthermore, numbers for identifying components are used in different contexts, and a number used in one context does not necessarily indicate the same configuration in another context. Furthermore, a component identified by a certain number does not prevent the component from also having the function of a component identified by another number.

[0126] In this specification, when a certain component is referred to as "comprising," it does not mean that other components are excluded, but rather that other components may be further included, unless this is inconsistent with the content of the present invention.

[0127] 5. Supplementary Notes The embodiments disclosed herein also include the following.

[0128] [Appendix 1] A main body having a first internal electrode layer, a second internal electrode layer, and a ceramic layer disposed between the first internal electrode layer and the second internal electrode layer and formed from a ceramic material to which a sintering aid containing a sintering aid element as a main component has been added; a first external electrode provided on the body so as to be electrically connected to the first internal electrode layer; a second external electrode provided on the main body so as to be electrically connected to the second internal electrode layer; Equipped with The first internal electrode layer has an electrode portion which is a sintered body of a main component metal element, and a non-electrode portion which is surrounded by the electrode portion and contains the sintering aid element, a first concentration indicating a concentration of the sintering aid element in the non-electrode portion is higher than a second concentration indicating a concentration of the sintering aid element at an interface between the first internal electrode layer and the ceramic layer; Multilayer ceramic capacitor. [Appendix 2] the ceramic layer includes a plurality of crystal grains that are a sintered body of the ceramic material; The first concentration is higher than a third concentration indicating a concentration of the sintering aid element at the grain boundaries of the crystal grains. 2. The multilayer ceramic capacitor according to claim 1. [Appendix 3] The third concentration is greater than the second concentration. 4. A multilayer ceramic capacitor as described in appendix 2. [Appendix 4] The first concentration is 10 at% or more. 4. The multilayer ceramic capacitor according to claim 1, [Appendix 5] The second concentration is 0.5 at% or less. 5. The multilayer ceramic capacitor according to claim 1, [Appendix 6] The third concentration is 0.5 at% or less. 10. The multilayer ceramic capacitor according to claim 1 or 2. [Appendix 7] a ratio of the first concentration to the third concentration is 10 or greater; 10. The multilayer ceramic capacitor according to claim 1 or 2. [Appendix 8] An intermediate layer is provided between the first internal electrode layer and the ceramic layer, and the intermediate layer includes a secondary element different from the main component metal element. the secondary element is at least one element selected from the group consisting of As, Au, Co, Cr, Cu, Fe, In, Ir, Mg, Os, Pd, Pt, Re, Rh, Ru, Se, Sn, Ge, Te, W, Y, Ag, and Mo; a fourth concentration indicating a concentration of the sub-element in the intermediate layer is higher than a fifth concentration indicating a concentration of the sub-element in the first internal electrode layer; 8. The multilayer ceramic capacitor according to claim 1, [Appendix 9] In the ceramic layers, the number of the crystal grains interposed between the first internal electrode layers and the second internal electrode layers is 3 or less. 4. A multilayer ceramic capacitor as described in appendix 2. [Appendix 10] A circuit module comprising the multilayer ceramic capacitor according to any one of claims 1 to 7. [Appendix 11] 11. An electronic device comprising the circuit module according to claim 10. [Appendix 12] A preparation step of preparing a green laminate including a ceramic green sheet containing a sintering aid and an internal electrode pattern provided on a first surface and a second surface of the ceramic green sheet; a first heat treatment step of heating the green laminate to a first top temperature and holding the green laminate at the first top temperature for a first holding time to obtain a sintered laminate from the green laminate; a second heat treatment step of holding the sintered laminate at a second top temperature lower than the first top temperature for a second holding time after the first heat treatment step; Equipped with A method for manufacturing a multilayer ceramic capacitor, in which, in at least one of the first heat treatment step and the second heat treatment step, an internal electrode layer having an electrode portion and a non-electrode portion is formed from the internal electrode pattern, and the sintering aid is moved to the non-electrode portion. [Appendix 13] The internal electrode pattern contains a main component metal element and a sub-element (wherein the sub-element is at least one element selected from the group consisting of As, Au, Co, Cr, Cu, Fe, In, Ir, Mg, Os, Pd, Pt, Re, Rh, Ru, Se, Sn, Ge, Te, W, Y, Ag, Mo, and Ge), In the first heat treatment step, the internal electrode layer is formed from the internal electrode pattern, a ceramic layer is formed from the ceramic green sheet, and an intermediate layer containing the sub-element at a higher concentration than the internal electrode layer is formed between the internal electrode layer and the ceramic layer. The manufacturing method described in Appendix 12. [Appendix 14] The first heat treatment step includes a step of forming an electrode portion including a sintered body of the main component metal element, and transferring the sintering aid in a liquid phase to a non-electrode portion surrounded by the electrode portion, The method for producing the present invention described in Appendix 12 or Appendix 13. [Appendix 15] The second heat treatment step includes a step of further transferring the sintering aid in a liquid phase to the non-electrode portion. The method according to any one of claims 12 to 14. [Explanation of symbols]

[0129] 1. Multilayer ceramic capacitors 10. Main Unit 11 Ceramic layer 21 1st internal electrode layer 22 Second internal electrode layer 21a 1st electrode part 21b First non-electrode part 22a 2nd electrode part 22b Second non-electrode part 31 1st external electrode 32 2nd external electrode 40 Grains 45 Grain boundaries 47 First interface layer 48 Second interface layer 51 First Middle Class 52 Second Middle Class 80 Liquid phase components

Claims

1. A main body having a first internal electrode layer, a second internal electrode layer, and a ceramic layer disposed between the first internal electrode layer and the second internal electrode layer and formed of a ceramic material to which a sintering aid containing a sintering aid element as a main component has been added; a first external electrode provided on the main body so as to be electrically connected to the first internal electrode layer; a second external electrode provided on the main body so as to be electrically connected to the second internal electrode layer; Equipped with The first internal electrode layer has an electrode portion which is a sintered body of a main component metal element, and a non-electrode portion which is surrounded by the electrode portion and contains the sintering aid element, a first concentration indicating a concentration of the sintering aid element in the non-electrode portion is higher than a second concentration indicating a concentration of the sintering aid element at an interface between the first internal electrode layer and the ceramic layer; Multilayer ceramic capacitor.

2. the ceramic layer includes a plurality of crystal grains that are a sintered body of the ceramic material; The first concentration is higher than a third concentration indicating a concentration of the sintering aid element at the grain boundaries of the crystal grains. The multilayer ceramic capacitor according to claim 1 .

3. The third concentration is higher than the second concentration. The multilayer ceramic capacitor according to claim 2 .

4. The first concentration is 10 at% or more.

3. The multilayer ceramic capacitor according to claim 1 or 2.

5. The second concentration is 0.5 at% or less.

3. The multilayer ceramic capacitor according to claim 1 or 2.

6. The third concentration is 0.5 at% or less. The multilayer ceramic capacitor according to claim 2 .

7. a ratio of the first concentration to the third concentration is 10 or more; The multilayer ceramic capacitor according to claim 2 .

8. An intermediate layer is provided between the first internal electrode layer and the ceramic layer, and the intermediate layer contains a sub-element different from the main component metal element. The subelement is at least one element selected from the group consisting of As, Au, Co, Cr, Cu, Fe, In, Ir, Mg, Os, Pd, Pt, Re, Rh, Ru, Se, Sn, Ge, Te, W, Y, Ag, and Mo; a fourth concentration indicating a concentration of the sub-element in the intermediate layer is higher than a fifth concentration indicating a concentration of the sub-element in the first internal electrode layer; 3. The multilayer ceramic capacitor according to claim 1 or 2.

9. In the ceramic layers, the number of the crystal grains interposed between the first internal electrode layers and the second internal electrode layers is 3 or less. The multilayer ceramic capacitor according to claim 2 .

10. A circuit module comprising the multilayer ceramic capacitor according to claim 1 .

11. An electronic device comprising the circuit module according to claim 10.

12. A preparation step of preparing a green laminate including a ceramic green sheet containing a sintering aid and an internal electrode pattern provided on a first surface and a second surface of the ceramic green sheet; a first heat treatment step of heating the green laminate to a first top temperature and holding the green laminate at the first top temperature for a first holding time to obtain a sintered laminate from the green laminate; a second heat treatment step of holding the sintered laminate at a second top temperature lower than the first top temperature for a second holding time after the first heat treatment step; Equipped with In at least one of the first heat treatment step and the second heat treatment step, an internal electrode layer having an electrode portion and a non-electrode portion is formed from the internal electrode pattern, and the sintering aid is moved to the non-electrode portion. A method for manufacturing a multilayer ceramic capacitor.

13. The internal electrode pattern contains a main component metal element and a sub-element (wherein the sub-element is at least one element selected from the group consisting of As, Au, Co, Cr, Cu, Fe, In, Ir, Mg, Os, Pd, Pt, Re, Rh, Ru, Se, Sn, Ge, Te, W, Y, Ag, Mo, and Ge), In the first heat treatment step, the internal electrode layer is formed from the internal electrode pattern, a ceramic layer is formed from the ceramic green sheet, and an intermediate layer containing the sub-element at a higher concentration than the internal electrode layer is formed between the internal electrode layer and the ceramic layer. The method of claim 12.

14. The first heat treatment step includes a step of transferring the sintering aid to the non-electrode portion surrounded by the electrode portion, the non-electrode portion including the sintered body of the main component metal element being formed at the electrode portion, The method of claim 13.

15. The second heat treatment step includes a step of further transferring the sintering aid to the non-electrode portion. The method of claim 14.

Citation Information

Patent Citations

  • Dielectric ceramic composition, and laminated type electronic component

    JP2009084111A